Zinc Phthalocyanine Tetrasulfonate-Loaded Ag@mSiO2 Nanoparticles for Active Targeted Photodynamic Therapy of Colorectal Cancer - Montaseri, Hanieh; Simelane, Nokuphila Winifred Nompumelelo; Abrahamse, Heidi (Frontiers in Nanotechnology, 2022)
Colorectal cancer has high morbidity and mortality rate with a high level of metastasis and recurrence due to the poor therapeutic effects. Photodynamic therapy (PDT) as an emerging clinical modality for cancer treatment provides remarkable advantages over existing treatments by generating reactive oxygen species (ROS) through light irradiating photosensitizers (PSs) in the presence of oxygen. PDT can induce immunity against recurrence and destruction of metastases. The application of nanoparticles (NPs) in targeted cancer therapy is coming to light to circumvent the limitations associated with low physiological solubility and lack of selectivity of the PS towards tumor sites. In this in vitro study, we proved the added value of NP systems on PS efficacy and a tumor-targeting ligand. Using core/shell Ag@mSiO2 NPs loaded with ZnPcS4 PS and folic acid (FA), stronger cellular localization in the human colorectal cancer cell line (Caco-2) was observed compared to the passive NC and free PS. Additionally, light-induced photodynamic activation of the ZnPcS4/Ag@mSiO2-FA nanoconjugate (NC) elicited a strong cytotoxicity effect mediated by post-PDT. The results also revealed that the active NC was able to decrease the cell viability remarkably to 38.0% ± 4.2 *** compared to the passive NC (67.0% ± 7.4*) under 0.125 µM ZnPcS4 (IC50). More importantly, the actively targeted NC induced apoptosis where cell cycle analysis elaborated on cell death through the G0 phase, indicating the final NC’s efficacy 20hrs post-PDT treatment.